Pharmacist-Led Education for Final Year Medical Students: A Pilot Study - Mokrzecki, Sophie; Pain, Tilley; Mallett, Andrew; Perks, Stephen (Frontiers in Medicine, 2021)
Background: Prescribing is a core skillset for medical officers. Prescribing errors or deficiencies can lead to patient harm and increased healthcare costs. There is an undefined role for pharmacist-led education to final year medical students to improve prescribing skills. Aim: Assess if pharmacist-led education on prescription writing improves the quality and safety of final year medical students’ prescribing skills. Method: Participants and intervention: Final year medical students were randomised into tutorial (TG) or non-tutorial groups (NTG) and assessed pre- and post- intervention. TG received education by a clinical pharmacist and pharmacy educator using case-based learning. NTG received no additional training as per usual practice. Following the pre-test, all students completed a three-week tertiary hospital medical ward placement. Students completed the post-test following placement and after the TG participated in the intervention. Student assessment: Assessment included writing Schedule 4 (S4, prescription only), Schedule 8 (S8, controlled drug), S4 streamline (S4SL), and Mixed case (S4 and S8) prescriptions. Results: At baseline, there were no significant differences between TG and NTG for overall scores or proportion of passes. Post intervention scores significantly improved in TG (p=0.012) whereas scores significantly decreased in the NTG (p=0.004). The overall proportion of passes was significantly higher in the TG than NTG (p<0.001). Conclusion: Education by a clinical pharmacist improved short-term prescribing skills of final year medical students in this study. Students learning primarily experientially from peers and rotational supervisors showed decreased prescribing skills. We propose pharmacist-led education on prescription writing should be further evaluated in larger studies across more student cohorts and for longer periods of follow up time to clarify whether such an educational model could be included in future medical school curricula.